2023
DOI: 10.1038/s41598-023-34346-x
|View full text |Cite|
|
Sign up to set email alerts
|

Equivalent running leg lengths require prosthetic legs to be longer than biological legs during standing

Abstract: We aimed to determine a method for prescribing a standing prosthetic leg length (ProsL) that results in an equivalent running biological leg length (BioL) for athletes with unilateral (UTTA) and bilateral transtibial amputations (BTTA). We measured standing leg length of ten non-amputee (NA) athletes, ten athletes with UTTA, and five athletes with BTTA. All athletes performed treadmill running trials from 3 m/s to their maximum speed. We calculated standing and running BioL and ProsL lengths and assessed the r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…A recent study found that the forward distance covered by the participant's center of mass (COM) during the contact period is a pivotal factor influencing peak running speed ( 52 ). Another highlighted the impact of stiffness on leg length specifically during midstance, making it important for athletes with unilateral amputation ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that the forward distance covered by the participant's center of mass (COM) during the contact period is a pivotal factor influencing peak running speed ( 52 ). Another highlighted the impact of stiffness on leg length specifically during midstance, making it important for athletes with unilateral amputation ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further, an increase in midsole thickness may result in between a 1–3% increase in overall limb length and enhance stride length, the consequences of which are increasingly studied in the context of athletes with transtibial amputations. Although the topic is currently keenly debated ( Taboga et al, 2020 ; Beck, Taboga & Grabowski, 2022 ; Zhang-Lea et al, 2023 ; Weyand et al, 2022 . ), there is evidence of an association between longer leg length and faster maximal velocity ( Weyand et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%